Pink blood: la violence homophobe au Canada : essai - Janoff, Douglas (Triptyque, 2007)
Essai traduit de l'anglais sous la direction de Diane Archambault Livre unique en son genre, Pink Blood est la première étude de cas de portée nationale à paraître en français sur le thème de la violence homophobe. Fruit de neuf ans de recherche, il couvre plus de 350 agressions et quelque 120 homicides perpétrés au Canada sur la personne de gais et de lesbiennes entre 1990 et 2004. L’ouvrage analyse avec minutie l’impact de la violence homophobe dans une démocratie qui s’enorgueillit d’accorder « l’égalité » à tous ses citoyens… Certains Canadiens seraient-ils plus égaux que d’autres? De Whitehorse à St. John’s en passant par Montréal et Québec, l’auteur pose les questions suivantes: Comment la police fait-elle enquête sur ces crimes et comment les enregistre-t-elle? Quel traitement leur réserve le système judiciaire? Comment les médias présentent-ils ces incidents? Quels programmes et politiques ont soulevé la question de la violence homophobe et transphobe et quels sont ceux qui sont passés à côté de la question? La version anglaise de l’ouvrage, parue en 2005 aux Presses de l’Université de Toronto, a été retenue dans le programme d’enseignement de plusieurs facultés universitaires canadiennes.
Section: 411 pages ; 23 cm
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; histoire et politique; homophobie; hétérosexisme; premier cycle; périodes historiques; régions géographiques; soc2014; systèmes d'oppressions; thématiques; violences

La réflexion queer : apports et limites - Lamoureux, Diane (Dialogues sur la troisième vague féministe, 2005)
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; fem1000; histoire et politique; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Mariage gai: les coulisses d'une révolution sociale - Larocque, Sylvain (Flammarion, 2005)
Certains l’ont vu comme le plus important débat social de notre époque, c’est en tout cas une question déchirante, sur laquelle ont dû se pencher la plupart des pays occidentaux. Ce livre raconte l’histoire inédite du mariage gai au Canada : la bataille des arguments juridiques et politiques, les stratégies secrètes et surtout les jeux de coulisses qui ont conduit à cette nouvelle avancée des droits de la personne.Pour témoigner des motivations des couples qui ont amorcé le mouvement, puis des juges et des politiciens qui ont pris le relais, Sylvain Larocque s’appuie sur une trentaine d’entrevues exclusives, y compris avec le premier ministre Paul Martin, des ministres, des conseillers politiques et des avocats. On saisit ce qui a convaincu Jean Chrétien et son successeur d’aller de l’avant avec cette véritable « patate chaude » ; on comprend ce qu’ont ressenti les opposants face à cette redéfinition d’une institution millénaire ; on mesure l’ampleur d’une controverse qui en appelait aux convictions intimes de chacun. Suivant Sylvain Larocque Sylvain Larocque est correspondant parlementaire de La Presse Canadienne à Ottawa. Il a suivi de près les tractations juridico-politiques ayant entouré le mariage homosexuel.
Section: 337 pages ; 23 cm
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; histoire et politique; hétérosexisme; identités LGBTQIA2+; mariage; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Aimez-vous le queer? - Schehr, Lawrence R. (Rodopi, 2005)
Lawrence Schehr's introduction to this collection of essays covers key landmarks in twentieth-century representations of homosexuality in French literature and culture. Beginning with Gide's and Proust's classical and aristocratic representations of homosexuality, subdued within discourses of power and language consonant with the turn of the century, Schehr proceeds to identify the literary and cinematic innovations of Cocteau and Genet as united in their respective revolt against the totalizing structures and discourses of their illustrious predecessors. After discussing the Second World War, the consumerism of the 1960s, and the emerging ‘culture gay’, Schehr fast-forwards to the advent of the paradox of queer theory in the 1990s, highlighting its theoretical (mis)appropriations, from the positive critique of heteronormativity to its insignificance ‘pour le séropositif mourant dans un lit d'hôpital’ (p. 10), acknowledging along the way that queer theory is both ‘made in the USA’ (p. 11) and subject to that continent's imperializing tendencies and ancillary oversights. The editor promises queer readings of French literature and film, but then proffers post-queer readings. Many of the contributions are stimulating and rich in insights. Owen Heathcote's study of the military uniform as both mask and precursor of the collapse of masculinity in novels by Balzac and the cinema of Claire Denis earmarks the uniform as the queerizing stuff of maleness. James Williams's exploration of Jean Cocteau's influence on the cinema of Jean-Luc Godard also unearths a queerization at the heart of Godard's aesthetic creation. In a fascinating contribution, Elizabeth Stephens deconstructs the ‘wall’ of repression and solitude (and its associations with closeted representations of homosexuality) in order to expose the ‘fissures dans les murs genetiens’ (p. 133), demonstrating how Genet subverts categories of heteronormative language in the pursuit of repressed homoerotic desire. Drew Jones conducts a thoroughly lucid exegesis of the distinction between sexual desire (act) and homosexual ‘identity’ in Genet's Querelle de Brest. Countering the Sartrean notion that Genet's treatment of homosexuality (as value in crime and disgust against authority) is not existential (‘homosexuel en soi’ but not ‘pour soi’), Jones argues that Querelle breaks free of essentialist homosexuality by resisting the naming and categorizing hegemony of an Identity as ‘pederast’ that society has conferred on him. It would have been a treat to see how this collection would have evolved had the ‘projet scientifique’ first envisaged been followed through; this ‘projet’ clearly reflected the earlier symmetry of Schehr's tripartite schematization of homosexual cultural production from Proust to queer, but I suspect would have given the collection a different direction. The articles are the collection's real focus, and their value for students and academics with interests in gay and lesbian cultural production in France is unquestionable.
Section: 158 pages ; 24 x 17 cm
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; histoire et politique; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Lesbianisme et féminisme : histoires politiques - Chetcuti, Natacha; Michard, Claire (L'Harmattan, 2003)
Cet ouvrage est le premier en France ayant pour objectif de rendre compte de l'interdépendance historique des mouvements lesbiens et des mouvements féministes à partir du point de vue de différents courants du lesbianisme. Il montre que l'histoire de la pensée lesbienne et féministe, des années 1970 à nos jours, est marquée par des alliances, des tensions et des ruptures qui ont des répercussions tant du côté des études universitaires que du côté des pratiques militantes. Il montre aussi que le contenu politique du lesbianisme, dans sa mise en cause de l'ordre établi, est constamment occulté.
Le texte de Brossard, Louise (2003). « Adrienne Rich et Monique Wittig : un point de départ pour penser l’hétérosexualité et les rapports sociaux de sexe » a été donné en lecture au cours POL4212.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; approches et analyses; cours; discours dominant; histoire et politique; hétérosexisme; lesbianisme; militance; pol4212; premier cycle; périodes historiques; systèmes d'oppressions; thématiques

Le mouvement gai et lesbien américain face au SIDA - Marche, Guillaume (L'Homme & la Société, 2002)
Divided between essentialism and constructivism, the mobilization of united-statesian homosexuals becomes a real social movement when it goes beyond the opposition between integrationism and differentialism. Thanks to a complex identity forged by ACT-UP, it has been able in this way to resist AIDS. A comparison between San Francisco and New York shows that the initiative comes from the bottom up. Collective action is most effective as it takes account of differences (such as ethnicity) between homosexuals. This requirement has been dictated by the evolution of AIDS since the 1990s. It is, therefore, in stressing the subjectivity of the actors that the gay and lesbian movement can continue and contribute to social change in the United States.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; shm4000; systèmes d'oppressions; thématiques; états-unis

L'invention de l'hétérosexualité - Katz, Jonathan (EPEL, 2001)
L'auteur retrace l'histoire du concept d'hétérosexualité. Il analyse les textes d'auteurs comme Freud, Richard von Krafft-Ebing, Michel Foucault, Betty Friedan ou Kate Millet. Il nous montre que la distinction homosexuel/hétérosexuel ne repose pas sur une nature immuable mais constitue une façon récente de classer et de juger la société. [SDM].
Section: 236 pages ; 21 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; analyse de discours; approches et analyses; cours; discipline; discours dominant; europe; france; his4860; histoire; histoire et politique; homosexualité; hétérosexisme; hétérosexualité; identité sexuelle; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sex1181; sex1183; sexologie; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; épistémologie

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Section: 165, [2] p
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal - Demczuk, Irène; Remiggi, Frank William (VLB, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; violences

Lessons from the damned: queers, whores, and junkies respond to AIDS - Stoller, Nancy E. (Routledge, 1998)
"Lessons from the Damned challenges the notion that public health theories and official organizations have the greatest impact on the fight against AIDS. Instead, Stoller looks closely at the ways the most disenfranchised - the poor, people of color, drug users, gay men and lesbians, and women - have built social movements to fight the epidemic. Drawing upon extensive ethnographic research and the words of the activists themselves, as well as the literature of social movements and theories of bureaucracy, Stoller offers guidelines for dealing with diversity and conflict and also with both theoretical and practical perspectives on cross-community and international organizing."–BOOK JACKET.
Section: xvi, 175 pages : illustrations ; 24 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; capitalisme; care; cours; discipline; histoire et politique; hétérosexisme; justice sociale; militance; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; sida; soc2014; sociologie; sofia; systèmes d'oppressions; thématiques; états-unis

The rise of a gay and lesbian movement - Adam, Barry D. (Twayne, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis